2015
DOI: 10.1016/j.memsci.2015.03.089
|View full text |Cite
|
Sign up to set email alerts
|

Engineered iron/iron oxide functionalized membranes for selenium and other toxic metal removal from power plant scrubber water

Abstract: The remediation of toxic metals from water with high concentrations of salt has been an emerging area for membrane separation. Cost-effective nanomaterials such as iron and iron oxide nanoparticles have been widely used in reductive and oxidative degradation of toxic organics. Similar procedures can be used for redox transformations of metal species (e.g. metal oxyanions to elemental metal), and/or adsorption of species on iron oxide surface. In this study, iron-functionalized membranes were developed for redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…In our previous work, PAA tended to form a thin layer on the top of the membrane surface and block membrane pores, when immersing membrane in the polymer solution before heat treatment [52]. To diminish the formation of the PAA top layer, the PVDF membrane was placed in a Büchner funnel, which was then connected to a Büchner flask with a tube (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, PAA tended to form a thin layer on the top of the membrane surface and block membrane pores, when immersing membrane in the polymer solution before heat treatment [52]. To diminish the formation of the PAA top layer, the PVDF membrane was placed in a Büchner funnel, which was then connected to a Büchner flask with a tube (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the solution after acid digestion of the Fe x O y functionalized membrane showed an iron content of 12 g/m 2 of the membrane. Iron content in the membrane matrix can be increased by repetitive ion exchange cycles, with Na and Fe as demonstrated in our earlier study [44]. For this study, only one cycle of ion exchange was performed with the PAA functionalized membrane.…”
Section: Resultsmentioning
confidence: 87%
“…The observed lower permeability for functionalized membrane can, therefore, be explained by the lower volume of pores for water to flow through. In our earlier study, an excess of PAA layer on membrane surface was observed by studying surface morphology using the depth profile using X-ray photoelectron spectroscopy [44]. The excess of PAA layer on the membrane surface is due to polymerization of residual acrylic acid on the membrane surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized to be very efficient, but regeneration of the adsorbent produces a concentrated solution that requires further treatment (Merrikhpour and Jalali 2013;Ahmad et al 2015). Processes involving membranes have also been considered for the treatment of wastewater containing heavy metals (Meeks et al 2013;Gui et al 2015). Such techniques have been demonstrated to be very efficient for the removal of ions, but the large energy demand due to the high pressure required in the process is still a challenge.…”
Section: Response Surface Analysis For the Average Energy Consumptionmentioning
confidence: 99%